The mediating effect of microfinancing on access to finance and growth of microenterprises: Evidence from the Philippines - Imelda T. Angeles; Maria Socorro P. Calara; Allan B. de Guzman (Journal of Global Entrepreneurship Research, 2019)
Undoubtedly, microenterprises play a critical role in the development of the economy. Comprising a dominant share in the industry, microenterprises help to alleviate poverty and unemployment. However, the growth of microenterprises remains a global challenge. A number of scholars have attributed the growth of microenterprises to accessibility of finance; however, microfinancing is equally significant in the initiative of owners to expand. This study aims to examine how microfinancing mediates the effect of access to finance on the growth of microenterprises. A survey result from a dataset of 582 microenterprises from the Philippines was used for correlation, regression, and mediation analyses. The results suggest that the impact of access to finance on the growth of microenterprises is heightened when microfinancing is maximized. However, the owners' preferences toward internal financing limit the ability to expand. Thus, the issue of stagnation is a result of the owners' isolation to external financing. The results highlight the need for a more holistic approach to enterprise growth than merely facilitating access to finance. The study recommends aspects such as literacy and competitiveness as factors other than access to capital as enablers of growth. The results may challenge policymakers to enhance the existing policy frameworks further and provide more skills-enhanced income opportunities. Further, an experimental research using an intervention may help discover how to overcome stagnancy of micro and small firms.
Keywords: 650; Microenterprises; Microfinancing; Access to finance; Microenterprise growth